Evaluation of Physical Properties and Color characteristics of Millets based Cookies blended with Carrot-powder - Vipin Kumar Verma (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: The study focused on determining changes in diameter, thickness, weight, spread ratio, and color parameters (L*, a*, b*) using standard analytical methods. The experiment also aimed to assess the sensory quality of cookies formulated with varying levels of carrot powder to identify the most acceptable blend. Material and Methods: Millet-based cookies were prepared by incorporating different levels of carrot powder (T0 –T4 treatments). The dough was mixed, shaped, and baked under standard conditions. Physical properties such as diameter, thickness, weight, and spread ratio were determined using standard methods. Color values (L*, a*, b*) were measured with a colorimeter. Sensory evaluation was conducted by a semi-trained panel using a 9-point hedonic scale to assess overall acceptability. Result and Discussion: Incorporation of carrot powder into millet-based cookies significantly influenced their physical and color characteristics. The diameter decreased slightly from 5.73 cm (T0 ) to 5.60 cm (T4 ), while thickness and weight increased from 0.92 cm to 1.14 cm and 13.91 g to 17.71 g, respectively. The spread ratio showed a declining trend from 6.22 (T0 ) to 4.91 (T4 ). Color values indicated reduced lightness (L*) and variable redness (a*) and yellowness (b*) with increasing carrot powder levels. Sensory evaluation revealed that cookies from treatment T3 achieved the highest overall acceptability, whereas T4 scored the lowest. Conclusion: Adding carrot powder to millet-based cookies affected their physical, color, and sensory qualities, with moderate addition (T3) being most preferred by panelists.